Designing A Low-Cost Educational Learning Kit Based On Arm Cortex-M Cores - Loh, Qing Zhen (Universiti Sains Malaysia, 2017)
In this project, a low-cost educational learning kit is designed and developed by using the NXP FRDM-KL25Z, an ARM processor based development board as a learning platform. Some peripherals is interfaced with the NXP FRDM-KL25Z to learn the embedded systems programing in C++. The main objective of this project is to design a low-cost educational learning kit for ARM processor and develop a step by step tutorial. Although the ARM processor based development board is not difficult to get now, but the tutorial for it is hard to get and understand by the beginner. A lot of compiler are compatible to the same development board nowadays. It is actually a problem to the beginner on which compiler and what platform to choose as the kick start on the embedded system programing. With the educational learning kit and the step by step tutorial to help them, they can have a better understanding to the topic learned. Some exercises are also provided after each topic to increase the understanding on that topic. The educational learning kit helped the beginner in understanding what to do with an ARM processor based development board including how to configure the compiler setting for different development board, how to include the external library to the compiler and so on. The educational kit is useful and important to help the beginner in learning the ARM processor based development board.